Pengaruh Kebijakan Dividen, Struktur Modal, Ukuran Perusahaan Dan Profitabilitas Terhadap Nilai Perusahaan Pada Perusahaan Keuangan Dan Perbankan Di Bursa Efek Indonesia Periode 2017-2020 - Mahdi Hendrich; Irsan; Zein Ghozali; Kemas Welly Angga Permana (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2024)
Company value reflects the present value of expected future earnings. Good financial management can maximize company value. This research aims to determine the influence of capital structure and company size on company value, the influence of dividend policy and profitability on company value. The research sample was 46 financial and banking companies that went public on the IDX. The method used is purposive sampling, namely a sampling method by determining certain criteria, namely financial and banking companies on the IDX that publish annual financial reports consistently in 2017-2020, financial and banking companies on the IDX that publish annual financial reports as of date December 31, and companies that have positive profitability values so that using the pooled data method (2017- 2020), the number of observations (n) = 168 is obtained. The data analysis method uses multiple regression. The research results show that there is no significant influence between dividend policy on company value, there is a negative and significant influence between capital structure on company value, there is a positive and significant influence between company size on company value, there is a positive and significant influence between profitability on company value.